Aspects Regarding Training Activity Analysis and Characteristics in the Romanian Educational System - Tița, Dumitrel-Victor; Bold, Nicolae; Popa, Doinița; Matei, Mirela-Georgiana; Trușcă, Claudia-Ionela (Didactica Danubiensis, 2023)
The continuous education is an important part of any national educational system. In this matter, we have developed a study whose aim is to explore and understand the continuous training of pre-university teachers in Romania. The study represents an opportunity to bring to the fore the importance of continuous teacher training, to identify their needs and requirements in terms of professional development and to promote innovative and relevant educational practices for the Romanian education system. The study was conducted in a specific period of time and on a representative sample, showing the importance of the training process in the educational field.